Pubertal Timing and Health-Related Quality of Life—A Cross-Sectional Study of Polish Adolescents - Zbigniew Izdebski; Alicja Kozakiewicz; Katarzyna Porwit; Michalina Aleksandra Gryglewska; Joanna Mazur (Pediatric Reports, 2025)
Background/Objectives: In research on the relationship between pubertal timing and adolescent health, more attention is typically given to early rather than late maturation, as well as the associated risk of engaging in health-compromising behaviors. The aim of this study was to assess changes in HRQL (health-related quality of life) depending on subjectively perceived pubertal timing, measured in five categories. Methods: A cross-sectional online survey was conducted in spring 2024 in a western region of Poland (N = 9411; mean age 15.15 ± 1.56 years). Mean KIDSCREEN-27 index scores were compared according to self-reported pubertal timing, and five relevant general linear models were estimated, adjusting analyses for respondents’ age, sex, and the remaining four HRQL scores. Results: In the study group, 49.0% of students assessed their pubertal timing as typical, 28.5% as earlier, and 22.5% as later compared to peers of the same sex. For all five KIDSCREEN-27 dimensions, adolescents who matured at a pace perceived as typical achieved the highest quality-of-life index scores. Significantly earlier or significantly later pubertal timing was associated with a notable decrease in these indices. Some significant interactions were identified between sex or age and pubertal timing as predictors of HRQL. The strongest association with pubertal timing was observed for the Psychological Well-being dimension, where differences unfavorable to older age groups were additionally linked to delayed pubertal timing. Conclusions: Greater awareness of the relationship between perceived pubertal timing and adolescents’ well-being is warranted among preventive care physicians, parents, and school psychologists and educators.